High-intensity light disrupts intracellular organelle dynamics via microtubule depolymerization - Zihao Zhang; Jian Han; Ke Wei; Shixi Chen (Scientific Reports)
Abstract Chromatophores provide an excellent model to study organelle transport as they specialize in the translocation of pigment granules in response to defined environmental signals. Our previous study revealed low-intensity light-induced xanthosomes aggregation is directly mediated by Opsin 3 in xanthophores of large yellow croaker (Larimichthys crocea). Herein, we report an incidental observation of prolonged (more than 40 min) high-intensity white light (HIWL) (10,000 lux, 3.86 mW/cm2) exposure induce xanthosomes dispersion. After dispersion by HIWL exposure, the xanthosomes remains the ability to aggregate under low-intensity light conditions. Both light-emitting diode (LED) sources at different wavelengths (blue light, λmax = 480 nm; red light, λmax = 686 nm) with identical brightness (10,000 lux) but varying absolute irradiance levels (3.86–22.2 mW/cm2) can induce xanthosome dispersion. Ex vivo illumination and pharmacological experiments on xanthophores revealed that HIWL-induced xanthosomes dispersion is irrelevant to signaling pathways typically associated with xanthosome movement, but mediated by microtubule depolymerization, which is due to extraordinary high level of intracellular Ca2+ released from IP3R calcium channel in endoplasmic reticulum. Interestingly, such a mechanism was also presented in HeLa and HEK293T cells exposed to HIWL. In summary, our results expand our understanding of the impact of high-intensity light on intracellular organelle transport and cytoskeleton.